Ludics, dialogue and inferentialism - Alain Lecomte (Baltic International Yearbook of Cognition, Logic and Communication, 2013)
In this paper, we try to show that Ludics, a (pre-)logical framework invented by J-Y. Girard, enables us to rethink some of the relationships between Philosophy, Semantics and Pragmatics. In particular, Ludics helps to shed light on the nature of dialogue and to articulate features of Brandom's inferentialism.
Keywords: semantics; pragmatics; logic